2022
DOI: 10.3390/pathogens11040457
|View full text |Cite
|
Sign up to set email alerts
|

Fecal DNA Virome Is Associated with the Development of Colorectal Neoplasia in a Murine Model of Colorectal Cancer

Abstract: Alteration of the gut virome has been associated with colorectal cancer (CRC); however, when and how the alteration takes place has not been studied. Here, we employ a longitudinal study in mice to characterize the gut virome alteration in azoxymethane (AOM)-induced colorectal neoplasia and identify important viruses associated with tumor growth. The number and size of the tumors increased as the mice aged in the AOM treated group, as compared to the control group. Tumors were first observed in the AOM group a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
3
1
Order By: Relevance
“…These data indicate that eukaryotic viruses other than bacteriophages had a specific role in CRC, which was different from what had been reported in the fecal virome [11]. Another animal study also showed an increase in certain bacteriophages' abundance with tumorigenesis [25], but their data came from the fecal virome, which results in different findings. Additionally, the viral community of CRC-A was different from that of CRC tissues, but not from that of HC tissues, which indicates that locally altered viruses in the mucosa might participate in CRC carcinogenesis.…”
Section: Discussioncontrasting
confidence: 72%
“…These data indicate that eukaryotic viruses other than bacteriophages had a specific role in CRC, which was different from what had been reported in the fecal virome [11]. Another animal study also showed an increase in certain bacteriophages' abundance with tumorigenesis [25], but their data came from the fecal virome, which results in different findings. Additionally, the viral community of CRC-A was different from that of CRC tissues, but not from that of HC tissues, which indicates that locally altered viruses in the mucosa might participate in CRC carcinogenesis.…”
Section: Discussioncontrasting
confidence: 72%
“… 4 Phages play a significant role in maintaining gut homeostasis and are hypothesized to induce oncogenesis by altering bacterial community composition and physiology. 15 , 17 , 51 In addition, alterations in the fecal virome have been linked to CRC, 16 , 19 , 51 yet more mechanistic studies are needed to explore whether they play a causative role . Here, we studied gut viral community composition of H. pylori -promoted colorectal cancer in tumor-prone Apc +/1638N compared with wild-type C57BL/6 mice, and found significant changes from Apc +/1638N mice in 12 weeks pi which reflects the early stage of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Dysbiosis of the GIT virome is associated with IBD and C. difficile infection [84], with substantial amounts of the bacteriophage microbiome absent or lessened in IBD patients, which may contribute to dysbiosis of bacterial commensals and eubiosis [85]. Furthermore, studies have altered the gut virome of mice with CRC-induced neoplasia [86]. Studies have investigated the use of phages against CRC-associated pathogens as biomarkers for CRC diagnosis [87].…”
Section: Intestinal Virome and Crcmentioning
confidence: 99%